3MT UPC 2019: Factors associated to injury severity of lower limbs in U.S firefighters during 2014 - Morales Silipo, Andrea Paula (2019)
Presentación realizada para el concurso Tesis en 3 minutos UPC 2019. / Carrera de Terapia Física